Ephrin-A2 affects wound healing and scarring in a murine model of excisional injury. Issue 3 (May 2019) - Wijeratne, Dulharie; Rodger, Jennifer; Stevenson, Andrew; Wallace, Hilary; Prêle, Cecilia M.; Wood, Fiona M.; Fear, Mark W.
Highlights: Ephrin signaling is important in wound healing. Ephrin A2 is important in collagen deposition and scar formation after injury. Understanding the role of ephrin and neuronal signals in wound repair may promote better intervention strategies. Abstract: Ephrin ligand/Eph receptor signaling is important in both tissue development and homeostasis. There is increasing evidence that Ephrin/Eph signaling is important in the skin, involved in hair follicle cycling, epidermal differentiation, cutaneous innervation and skin cancer. However, there is currently limited information on the role of Ephrin/Eph signaling in cutaneous wound healing. Here we report the effects of the Ephrin-A2 and A5 ligands on wound healing. Using Ephrin-A2 −/−, Ephrin-A5 −/− and Ephrin-A2A5 −/− transgenic mice, in vitro wound healing assays were conducted using isolated keratinocytes and fibroblasts. Ephrin-A2 −/−, Ephrin-A2A5 −/− and wild type mice with excisional wounds were used to analyze the impact of these ligands on wound closure, scar outcome, collagen orientation and re-innervation in vivo . The absence of the Ephrin-A2 and A5 ligands did not have any effect on dermal fibroblast proliferation or on fibroblast or keratinocyte migration. The loss of Ephrin-A2 and A5 ligands did not impact on the rate of wound closure or re-innervation after injury. However, changes in the gross morphology of the healed scar and in collagen histology of the scar dermis were observed in transgenic mice. Therefore Ephrin-A2 and A5 ligands may play an important role in final scar appearance associated with collagen deposition and structure.